(untitled) (THE ACADEMIA, 2026)
An experiment was conducted to know the effect of organic and inorganic fertilizers on morphological and yield characteristics of carrot cv. New Kuroda in Matikore, Khotang from 10th February, 2023 to 10th June, 2023. The experiment was laid out in Randomized Completely Block Design with seven treatments and three replications. Treatment consists of Control (T1), Prangarik mal @20 t/ha + Boron (T2), Poultry manure @6 t/ha + Boron (T3), Vermicompost @4 t/ha + Boron (T4), NPK @100:100:100 Kg/ha + Boron (T5), Neem cake @5 t/ha + Boron (T6), and Goat manure @ 15t/ha + Boron (T7). The result revealed that all growth and yield parameters was significantly influenced by applied fertilizers. The highest plant height was recorded in Prangarik mal + Boron, followed by Goat manure + Boron and minimum in Control. There was a significant difference in yield parameters among the treatments. The highest root yield was found in Prangarik mal+ Boron (42.43 t/ha), followed by Goat manure + Boron (27.44 t/ha), and the lowest yield in Control (7.77 t/ha). It can be concluded that the application of organic manures in combination with Boron can be practiced for obtaining better yield of Carrot.